Assessment of human physiology as indicators of stress when driving, biking and walking. (28th November 2022) - Melo, Wesley Cândido de; Brasil, Augusto César de Mendonça; Silva, Rita de Cássia
Human factors influence the choice of means of transport used for daily commuting, especially when the traveller perceives the effects of physical effort and stress. This study evaluated physiological indicators (blood pressure, galvanic skin response and heart and respiratory rate) during walking, cycling and driving private light vehicles, from the residential area to the University of Brasília, in the early morning and late afternoon, in six specific routes for walking, cycling and driving. The results show that non-motorised trips are less stressful than motorised ones, proving that when walking and cycling the traveller is free to obtain the best body conditions to reduce effort and stress, a fact explained by the cost of the minimum specific energy used during the shift.